Linguistic Identity Construal of Spanish Youth: ‘The Media Network Has Its Idols, But Its Principal Idol is Its Own Style Which Generates an Aura of Winning and Leaves the Rest in Darkness’ - Gogrichiani, Tamara Guliashvili (European Scientific Journal, ESJ, 2022)
The present investigation attempts to verify why and through what via the contact with English insertions in Spanish discourse changes the speech style and construes the linguistic identity of Spanish youth, even if they hardly speak English. In order to throw light on the above-mentioned hypothesis, Allan Bell’s (1977, 1984, 1991, 1997, 2001) Audience Design Theory was combined with an Attitudinal Experiment in which 250 students participated from Madrid Complutense University and Castilla la Mancha University. The students were asked to listen to two different recordings of females reading almost the same text, the difference being that one text contained English insertions and the other did not. As the culmination the experiment participants did the specially designed Likert Test. According to the results the following conclusions were reached: (i) The majority of the Attitudinal Experiment participants, the “new generation of Digital Natives” (Prensky 2001), accept that mass media is the major factor that influence their speech style; (ii) Spanish youth use English insertions in their Spanish discourse because they perceive someone who does as being young, modern, a cosmopolitan, a Spanish-English bilingual and someone trendy; (iii) Spanish youngsters use English insertions without being Spanish-English bilinguals; (iv) for the Attitudinal Experiment participants neither a particular speech style nor a sweet type of vice can measure cleverness of a speaker; (v) for the Attitudinal Experiment participants a sweet type of voice together with a particular speech style does matter.